Frontiers of the Roman Empire : = Grenzen des Römischen Reiches : the Antonine Wall = Der Antoninus Wall : a World Heritage Site - Breeze, David J (2022)
The Antonine Wall lay at the very extremity of the Roman world. This volume, presented in English and German, presents a concise introduction to the wall which is, in many ways, one of the most developed frontier in Europe. Perhaps of greatest significance is the survival of the collection of Roman military sculpture, the Distance Slabs.